Sibirskaja tradicija počitanija svjatyh mest v kontekste narodnoj istoričeskoj pamjati Siberian Folk Tradition of the Veneration of Sacred Places in the Context of People’s Historical Memory - Lyubimova, Galina V. (Studia mythologica Slavica, 2013)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The concept of holy places in the East Slavic tradition involves water springs, hills, trees, stones, wooden crosses and other landscape objects, of natural or artificial origin, endowed with a sacred status. As a rule, the “beginning” of the revered place is interpreted in the narratives as a result of activity of mythological characters, epic heroes or divine forces. Based on the author’s field materials, archival documents, publications of local periodicals and published works of the Siberian Old Believer writers, the article discusses the veneration of sacred places in tradition of the Russian population of Siberia. Special attention is paid to the history of one of the most revered places of the Altai Territory (the holy spring near the village of Sorochy Log). Its origin is referred to the historical events of the Civil War. Nevertheless, the analysis revealed that these events are comprehended in people’s historical memory according to the principles of mythological thinking.